A conciliação entre trabalho, família e estudo: desafios e estratégias dos trabalhadores-estudantes de administração da Unipampa - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This article sought to analyze how student-workers in the Unipampa Administration Course reconcile professional, family and academic activities during their undergraduate studies. To this end, a qualitative approach was conducted to analyze the relationship between the triple shifts of women and men who try to balance their professional, family and academic commitments. Data collection was carried out using three techniques: interviews with 11 student-workers working triple shifts; a focus group with 10 student-workers to collectively deepen the discussions of the first stage; and participant observation by this researcher, who is also a student-worker. The data show that, due to the diversity of profiles, such as student participants with or without children, assuming different roles as financial providers and primary caregivers, there is a variation in the way they experience conflicts between the three domains. The results indicate that the main challenges faced by student workers include lack of time, physical and mental fatigue, and emotional overload, often aggravated by the lack of institutional or family support. On the other hand, participants highlighted strategies such as organization, planning, and the use of support networks to try to deal with significant demands between genders: women, especially mothers, face more intense challenges due to social expectations related to family care, while men highlight different, but equally significant, difficulties related to the pressures to provide.
Balancing work, family and study: challenges and strategies for Unipampa’s management student workers
Keywords: Conflito trabalho; Estratégias de conciliação; Família e estudo; Tríplice jornada; Conciliação entre trabalho; Trabalhador-estudante; Family and study conflict; Conciliation strategies; Reconciliation between work; Triple shift; Family and study; Worker-student; CNPQ::CIENCIAS SOCIAIS APLICADAS